Desempenho reprodutivo de ovelhas morada nova submetidas a indução do estro pelo efeito macho - Lima, Rômulo Messias Diógenes (2013)
This study aimed to evaluate the efficiency of the male as the inductive effect of estrous activity in three categories (Nulliparous, Primiparous and Pluriparous) of crossbred ewes (MORADA NOVA X SPRD), and reproductive performance, from data obtained from manifestação estrus; intervalo between the introduction of the male and the onset of estrus; synchronization degree; repetition estrus; pregnancy rate; birth rate; twinning rate and prolificacy index. In two consecutive years were used, 81 animals, 02 male sheep (vasectomised a thug and a breeder) and 79 ewes divided into three categories, Nulliparous (Nul), Primiparous (Pri) and Pluriparous (Plu). During the first year, the females were subjected to the male effect method (EM), and the following year to the traditional method (MT), both with the breeding season of 42 days duration. Significant difference (P <0.05) was noted for the degree of synchronization of the EM with females (25.42%) compared to females with MT (10.17%). Females Nul and Pri subjected to male effect [30% (Nul), 42.10% (Pri)] were more responsive to the degree of synchronization, to the detriment of their counterparts in the traditional method [10% (Nul); 10.52 % (Pri)]. When specified for each category of females was noted superiority in results (P <0.05) within the same method for MT index prolificacy and twinning rate of females Plu (prolificacy: 2.25; twins: 95%) compared to Nul (prolificacy: 1.16; twinning: 15.79%) and Pri (prolificacy: 1.33; twinning: 33.33%). Also in the same method there was a significant difference (P <0.05) for the EM method. However, being greater for females Plu (prolificacy: 2.22; twinning: 88.88%) and Pri (prolificacy: 1.94; twinning: 72.22%) over the Nul (prolificacy: 1.39; twinning: 38.89%). Among the methods, EM Primiparous females (72.22%) were higher (P <0.05) females MT (33.33%) regarding twinning rate. As a conclusion it can be stated that the effect male appears feasible for synchronization of estrus in females up to first order of birth. Besides possibly cause better ovulation rate due to better results for twinning rate and prolificacy index.